Forage seed stakeholder workshop 12th May 2021: Addressing obstacles for thriving a forage seed sector in Tanzania - Ngunga, David; Nzogela, Beatus; Maleko, David; Mwendia, Solomon W.; Mwilawa, Angello; Omore, Amos O.; Notenbaert, An Maria Omer (Bioversity International and the International Center for Tropical Agriculture, 2021)
Livestock production constitutes a significant contribution to the economy and nutrition of many households in Tanzania. Despite the profound attributes of livestock in the nation, livestock sector is yet to attain its maximum level of production and productivity due to a number of challenges including insufficient forage quantity and quality. This culminates to poor animal performance especially during the dry seasons whereby availability of natural forages is limited and yet of poor nutritive value. In addition to a paucity of high quality forages, there is scarcity of improved forage planting materials including seeds and vegetative materials to provide livestock producers with improved forage suited to various ecological and agriculture contexts.